1966
DOI: 10.2118/1123-pa
|View full text |Cite
|
Sign up to set email alerts
|

Waterflood Pressure Pulsing for Fractured Reservoirs

Abstract: Conventional tvaterfiooding often is uneconomic in highly fractured reservoirs because of the gross bypassing of the reservoir oil by injected water. imbibition and pressure imlse flooding have been used in at [east one fractured reservoir in an attempt to achieve better oil recovery per. formtnce. This paper presents the results of laboratory fiOW tests conducted On large cores t? evaluate~!,e possib~e applicability of zhese methods (parncuiarly pressure pulse fioo(iing) to different types of reservoir system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Elkings and Skov (1963), one of the earliest references showing field results to cyclic waterflooding, already attribute the success of the process to end effects. Moreover, laboratory results as shown by Owens and Archer (1966) and Pooladi-Darvish and Firoozabadi (2000) demonstrate the influence of capillary forces in oil imbibition. Shchipanov et al (2008) also included the influence of compressibility difference on propagation velocity of the pressure pulse on the different fluid mainly in high frequency cycles.…”
Section: Introductionmentioning
confidence: 90%
“…Elkings and Skov (1963), one of the earliest references showing field results to cyclic waterflooding, already attribute the success of the process to end effects. Moreover, laboratory results as shown by Owens and Archer (1966) and Pooladi-Darvish and Firoozabadi (2000) demonstrate the influence of capillary forces in oil imbibition. Shchipanov et al (2008) also included the influence of compressibility difference on propagation velocity of the pressure pulse on the different fluid mainly in high frequency cycles.…”
Section: Introductionmentioning
confidence: 90%
“…One of the unknowns in the model is the driving capillary pressure P c SW j-this value can be estimated from the capillary tubes model. The capillary pressure in a capillary tube is expressed by p _2_acos9 (3.16) and the permeability of a bundle of tubes is given by Owens and Archer (1966) reported that the mobilities of the imbibing water and expelled oil on the core surface stayed equal during a counter-current capillary imbibition. If this conclusion is assumed to be true for water-gas imbibition, the mobility terms in Eq.…”
Section: Effect Of Temperature On Imbibitionmentioning
confidence: 99%
“…Initial applications were with water as an improved way of waterflooding (Owens and Archer 1966;Felsenthal and Ferrell 1967;Raza 1971). Shelton and Morris (1973) used rich hydrocarbon gases instead of steam to increase the reservoir energy (as a short-term benefit) and reduce oil viscosity (as a long-term benefit).…”
Section: Introductionmentioning
confidence: 99%